Health and fun the wonders of physical education - Dizer, Ronualdo U.; Ferrer, Hannah Eunice P.; Roque, Maryrose C.
Health and fun: the wonders of physical education is a textbook series from grade 1 to grade 6. PE has long been recognized as an essential component in educational program aimed towards the holistic development of our children. The production of this book demonstrates the commitment of Don Bosco Press, Inc. to help each child develop and maintain an optimum level of health and well-being and for the children to acquire knowledge, attitude, and the ability to maintain the state of well-being throughout life. All information in this textbook is based on the scientific knowledge, concepts, principles, facts of the following areas: growth and developmental characteristics of a child, developmentally based curriculum, knowledge relating to effective and efficient movement, movement concepts and skills, locomotor, nonlocomotor, and manipulative skills, games and movement activities, gymnastics and movement activities, and dance and movement activities. Lastly, the textbook series major goal is to assist each child to develop an optimum level of health and well-being and to acquire the attitude, knowledge, and movement skills that will lead to lifelong participation in enjoyable and wholesome physical activities